Deposition of Diamond-like Carbon and Carbyne Thin Film by Cathodic Plasma Electrolysis Process - A. Habibi; S.M. Mousavi Khoie; F. Mahboubi (Journal of Advanced Materials in Engineering, 2018)
By using cathodic plasma electrolysis, a thin film of diamond-like carbon and carbyne was produced on the  nickel surface. The ethanolic solution at different concentrations of 15, 30 and 50 vol% was used as the  electrolyte; the  produced carbon film was studied by using glow discharge optical emission spectroscopy, scanning electron microscopy, optical profilometer,  and surface enhanced Raman scattering. The results proved the  coating formation of 40-60 nm thick carbon materials on the  nickel surface. The intensity ratio of carbyne band to the amorphous carbon structure band in the  Raman spectroscopy was decreased from 1.o4 to 0.32 by an increase in ethanol concentration; this was related to the  reduction at the carbyne and the  increase of the diamond-like carbon content in the produced film. Also, the study of the  samples surface showed an increase in the  surface roughness from 520 to 750 nm by enhancing the ethanol concentration.